Analysis of the Effects of Human Capital Quality, Investment and Number of Labor on Financial Performance - Panjaitan, Nahdya Yohana; Bahtiar Fitanto (Journal of Development Economic and Social Studies, 2025)
North Sumatra education, as measured by the Average Length of School (RLS), has consistently increased in the 2018-2022 period. However, with a fairly high RLS rate compared to other provinces, the economic performance of North Sumatra Province grew slower than Jambi and South Sumatra Provinces. Likewise, the level of health also shows improvement. Other factors such as investment and the number of workers show that the number fluctuates every year in North Sumatra Province. This study aims to determine the influence of the quality of human capital, investment, and the number of labor on economic performance in North Sumatra Provincial Regencies/Cities. This study uses a panel data regression analysis method with a Fixed Effect Model test. The results of the analysis test showed that the human capital quality variable had a positive and significant effect on economic performance, while the investment variable and the number of labor had no effect. However, partially, all independent variables in this study had a positive and significant effect on the dependent variable, namely economic performance.